2006
DOI: 10.1051/0004-6361:20065296
|View full text |Cite
|
Sign up to set email alerts
|

Superclusters of galaxies from the 2dF redshift survey

Abstract: Aims. We use the 2dF Galaxy Redshift Survey data to compile catalogues of superclusters for the Northern and Southern regions of the 2dFGRS, altogether 543 superclusters at redshifts 0.009 ≤ z ≤ 0.2. Methods. We analyse methods of compiling supercluster catalogues and use results of the Millennium Simulation to investigate possible selection effects and errors. We find that the most effective method is the density field method using smoothing with an Epanechnikov kernel of radius 8 h −1 Mpc. Results. We derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(126 citation statements)
references
References 61 publications
4
121
0
1
Order By: Relevance
“…We used the B 3 spline kernel to calculate the density field. We chose a 8 h −1 Mpc scale smoothing for global densities (Einasto et al 2007). Details of the density calculation are given in Liivamägi et al (2011).…”
Section: Determining Environmental Densitiesmentioning
confidence: 99%
“…We used the B 3 spline kernel to calculate the density field. We chose a 8 h −1 Mpc scale smoothing for global densities (Einasto et al 2007). Details of the density calculation are given in Liivamägi et al (2011).…”
Section: Determining Environmental Densitiesmentioning
confidence: 99%
“…It has been shown that the morphological properties of galaxies depend on their large-scale cosmological environment (Einasto et al 2007a, and references therein). Both the local (group or cluster scale) and global (supercluster scale) environments influence galaxy morphology and their star-formation activity.…”
Section: Superclusters and Quasarsmentioning
confidence: 99%
“…The half-width of the B3 smoothing kernel was 16 h −1 Mpc, and the effective smoothing radius (the kernel halfwidth for which the density value differs considerably from zero) is 8 h −1 Mpc. This is an appropriate value for characterizing the global environment and superclusters (Einasto et al 2007a).…”
Section: Superclusters and Quasarsmentioning
confidence: 99%
“…Recent deep surveys of galaxies (as 2dFGRS and SDSS, see Colless et al 2003;Abazajian et al 2009) introduced a new era in the studies of the large-scale structure of the Universe, where systems of galaxies can be studied in unprecedended detail. A number of supercluster catalogues have been compiled with these data (Basilakos 2003;Einasto et al 2003a;Erdogdu et al 2004;Einasto et al 2006Einasto et al , 2007bLiivamägi et al 2010;Luparello et al 2011, and references therein).…”
Section: Introductionmentioning
confidence: 99%